The right to liberty : a pillar of freedom in a democratic society - Hamid, Abdul Ghafur@Khin Maung Sein (Sweet and Maxwell Asia, 2012)
All the international and regional human rights instruments, and national constitutions based on these instruments, acknowledge the ‘right to liberty’ as a fundamental human right and they are designed to protect the individual against arbitrary arrest or detention. With one significant exception, Article 9 of ICCPR, Article 5 of the European Convention on Human Rights (ECHR), Article 7 of the American Convention on Human Rights (ACHR) contain similar provisions. The distinctive feature of Article 5 of ECHR is that it defines exhaustively the cases in which a person may be deprived of his or her liberty. Article 10 of the ICCPR deals with certain rights of those deprived of their liberty. The humane treatment and the respect for the dignity of all persons deprived of their liberty is a basic standard that is of universal application.